Abusive supervision and job outcomes: a moderated mediation study. Issue 2 (6th August 2018) - Pradhan, Sajeet; Jena, Lalatendu Kesari
Abstract : Purpose: Based on the conservation of resources theory, the purpose of this paper is to investigate the linkage between abusive supervision (a workplace stressor) and subordinate's intention to quit by focusing on the mediating role of emotional exhaustion. The study also explores the conditional mediation model by testing the moderational role of perceived coworker support on the mediated abusive supervision-intention to quit relationship via emotional exhaustion. Design/methodology/approach: To test the proposed hypotheses, the study draws data from 382 healthcare employees working in several hospitals and clinics in the eastern and north-eastern states of India. The authors collected data on the predictor and criterion variables at two time points with a separation of three to four weeks in a reversed order to counter priming effect. Findings: The findings of the study reported that emotional exhaustion partially mediated the abusive supervision-intention to quit relationship. The result also supported the assertion that perceived coworker support will moderate the relationship between abusive supervision and subordinate's intention to quit. The authors also found support to the moderated mediation hypothesis, that suggest perceived coworker support will reduce the mediating effect of abusive supervision-intention to quit relationship via emotional exhaustion. Originality/value: This study is among few empirical investigations to investigate and report the interactional effect of perceived coworker support (a buffer) on the indirect relationship between abusive supervision and subordinate's intention to quit via emotional exhaustion.